Dually-dynamic covalent tetraPEG hydrogels end-linked with boronate ester and acylhydrazone groups. Issue 32 (2nd August 2022) - Michael, Charalambos; Apostolides, Demetris E.; Patrickios, Costas S.; Sakai, Takamasa
Abstract : TetraPEG hydrogels cross-linked via both boronic acid ester and acylhydrazone dynamic covalent bonds were developed. Adjustment of the fraction of each type of cross-link allows the fine-tuning of hydrogel behavior between self-repair and stability. Abstract : Well-defined dually dynamic hydrogels were prepared by end-linking four-armed poly(ethylene glycol) stars (tetraPEG stars) through two different types of dynamic covalent cross-links, boronates and acylhydrazones, leading to robust, self-healable materials. This required the prior end-functionalization of tetraPEG stars, originally bearing four hydroxyl terminal groups, with glucoronate, acylhydrazide and benzaldehyde groups, resulting in three differently end-functional star polymers. A first type of dually dynamic hydrogel resulted from the combination of the first two differently end-functionalized tetraPEG stars, cross-linked by 4-formylphenyl boronic acid, a small molecule bearing both an aldehyde and a boronic acid group, respectively complementary to the acylhydrazide and glucoronate end-groups of the two above-mentioned tetraPEG stars. For comparison, a singly-dynamic hydrogel cross-linked with only acylhydrazone groups was also prepared, as well as a double-like hydrogel combining the constituents of both of the above-mentioned hydrogels. All three types of hydrogels were prepared at three different pH values, 8.5, 10.5 and 12.5, leading to a total number of nine samples. All nine samples were investigated for their self-healing, mechanical, viscoelastic and aqueous swelling/degradation properties. This study sets the basis for the development of well-defined polymeric dynamic covalent hydrogels where their self-healing and stability can be readily tuned.